Programming as Design: The Role of Programming in Interactive Media Curriculum in Art and Design. - Amiri, Faramarz (International Journal of Art & Design Education, 2011)
The number of university undergraduate courses in the area of interactive media is increasing. Many of these courses are based in the schools of art and design that have traditionally valued and focused on developing the aesthetic and artistic design skills of their students. However, because of the rapid changes in new technology the relation between the technology and design has become complex. This poses new challenges for the educators in this field. The main challenge is defining the role of programming in the curriculum and the relationship between 'coding' skills and 'design' skills. The article examines different conceptual models of programming and suggests that the concept of programming as artistic and creative practice and 'programming as design' would be more suitable for the art and design curriculum.